Morphometric profile of achilles tendon in male - a cadaveric study (Nepal Medical College Journal, 2022)
The Achilles tendon is a conjoined tendon of gastrocnemius and soleus muscles and occasionally may have a small contribution from plantaris muscle. Despite being the strongest and thickest tendon in the body it is a frequent site of degenerative changes, inflammation and rupture. The main objective of this study was to measure and analyze the various parameters of Achilles tendon in cadavers. An observational, descriptive study was conducted from August 2021 to February 2022 in the Department of Human Anatomy of Nepal Medical College Teaching Hospital, Attarkhel, Gokarneshwor – 8, Kathmandu, Nepal which included forty lower limbs of twenty male cadavers. The various parameters recorded were (a) mean length of right Achilles tendon was 16.65 ± 1.72 cm, (b) mean proximal width of right Achilles tendon was 5.50 ± 1.07 cm, (c) mean proximal circumference of right Achilles tendon was 10.67 ± 2.20 cm, (d) mean distal width of right Achilles tendon was 2.22 ± 0.54 cm, (e) mean distal circumference of right Achilles tendon was 4.27 ± 0.67 cm, (f ) mean length of left Achilles tendon was 16.35 ± 1.49 cm, (g) mean proximal width of left Achilles tendon was 5.25 ± 0.88 cm, (h) mean proximal circumference of left Achilles tendon was 10.57 ± 1.78 cm, (i) mean distal width of left Achilles tendon was 2.05 ± 0.27 cm and mean distal circumference of left Achilles tendon was 4.0 ± 0.42 cm. The present morphometric evaluation of Achilles tendon in cadavers can be of substantial help to clinicians before determining its pathological conditions and can also be of help to surgeons during the surgical repair and reconstruction of damaged tendon.